2014
DOI: 10.1097/olq.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Would Targeting Increase Efficiency of Syphilis Partner Services Programs?—Data From New York City, Philadelphia, Texas, and Virginia

Abstract: Background Targeted partner notification (PN), or limiting PN to groups in which efforts are most successful, has been suggested as a potentially cost-effective alternative to providing PN for all syphilis case-patients. The purpose of this study was to identify index case characteristics associated with highest yield partner elicitation and subsequent case finding to determine whether some groups could be reasonably excluded from PN efforts. Methods We examined index case characteristics and PN metrics from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…Although these facilities play an important role in STD diagnoses, previous research has shown that compared with those seen at STD clinics, patients diagnosed at other facilities are less likely to be interviewed, name a sexual contact, and have a contact who is brought to treatment. 7,11 When stratified by diagnosing facility, improved outcomes for syphilis and gonorrhea cases diagnosed at STD clinics (vs. non-STD clinics) are observed for nearly all bars of the LAC index case continuum and elicited contact continuum, highlighting the need for continued and enhanced collaboration with the nonprofit and private sector to deliver STD field services activities (data not shown).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although these facilities play an important role in STD diagnoses, previous research has shown that compared with those seen at STD clinics, patients diagnosed at other facilities are less likely to be interviewed, name a sexual contact, and have a contact who is brought to treatment. 7,11 When stratified by diagnosing facility, improved outcomes for syphilis and gonorrhea cases diagnosed at STD clinics (vs. non-STD clinics) are observed for nearly all bars of the LAC index case continuum and elicited contact continuum, highlighting the need for continued and enhanced collaboration with the nonprofit and private sector to deliver STD field services activities (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…10 In fact, a recent analysis on the potential efficiencies of targeted partner elicitation efforts found contradictory results across 4 different LHJs. 11 There is a need for simple and replicable evaluation tools that LHJs can use to assess the overall efficacy of STD field services programs and guide the expenditure of limited resources. Although methodologies exist for the evaluation of field services activities, a common practice is to calculate a series of measures in a stepwise fashion so that the numerator of each measure serves as the denominator for the one that follows.…”
mentioning
confidence: 99%
“…During 2015 in North Carolina, 13% of syphilis investigations yielded a contact diagnosed with syphilis; our numbers of contacts named and new cases found were similar to those found in other studies. 8716 The number of index patients needed to interview (NNTI) to identify one new case of syphilis was 6.9; however, this number does not measure the full effort of syphilis investigations. Including interviews of both the index patients and their contacts, the TNTI was more than double this number (16.2).…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency has been quantified in many ways, 56 including as the number of treated partners per case interview, 7 likelihood and magnitude of future transmission, 4 and number of infected partners found per case. 89 More recently, calculation of the number of patients needed to interview to identify a new case of disease that is, number needed to interview (NNTI), has been used to assess the efficiency of partner investigation. 101112 The NNTI directly measures public health effort and can be used as a measure to compare intervention types across diseases.…”
mentioning
confidence: 99%
“…Predictors of PS success have been shown to vary by location. 22 Perhaps even more importantly, very few of the in-person interviews undertaken by King County DIS involved field investigations; most persons were interviewed in our STD clinic, either because they were diagnosed there or came to the clinic after being diagnosed. As a result, our procedures were dissimilar from many other areas where most interviews are conducted in the field and are initiated within days of a program learning of a new HIV or syphilis diagnosis.…”
Section: Discussionmentioning
confidence: 99%